Solvent-controlled synthesis of multicolor photoluminescent carbon dots for bioimaging. Issue 42 (2nd August 2019) - Yan, Yang; Xia, Longyu; Ma, Lan
Abstract : The synthesis and bioimaging of multicolor carbon dots from citric acid and urea. Abstract : Multicolor fluorescent carbon dots (CDs) have potential applications in multichannel detection and multicolor imaging. In this study, multicolor fluorescent CDs were synthesized by changing the solvent type and adjusting the reactant ratio. The four prepared CDs emitted bright and stable blue (B-), green (G-), yellow (Y-), and red (R-) fluorescence under a single UV light ( λ ex = 365 nm). The photoluminescence (PL) emission wavelengths changed from 445 nm for B-CDs to 620 nm for R-CDs, and therefore covered the entire visible spectrum. The absolute quantum yields for the B-, G-, Y-, and R-CDs were 27.3%, 31.1%, 22.9%, and 8.8%, respectively. Characterization of the CDs showed that the differences among the optical features of the four prepared CDs arise from the differences among the surface states and nitrogen-derived structures in the carbon core. The four prepared CDs all showed low toxicity and steady PL, and therefore have potential applications in both in vitro and in vivo imaging.